2006
DOI: 10.1111/j.1471-8286.2006.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of eight microsatellite loci in Leporinus macrocephalus (Characiformes: Anostomidae) and cross‐species amplification

Abstract: Leporinus macrocephalus is a species endemic to the Paraguay River basin and an important fishery resource, as well as a valuable species in aquaculture programs. A total of eight polymorphic microsatellite loci were isolated and characterized. A population survey was conducted involving 45 specimens whereby a large number of alleles (range 5 -17 among loci), a highly observed (0.1667 -0.6129) and an expected (0.6967 -0.9448) heterozygosity was detected, indicating its usefulness in population genetics studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 2 publications
(1 reference statement)
2
12
0
1
Order By: Relevance
“…Many studies have successfully demonstrated heterologous amplification of a target specie with SSR primer (Barbosa et al, 2006;Hatanaka et al, 2006, Morelli et al, 2007, thereby lowering the costs of future projects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have successfully demonstrated heterologous amplification of a target specie with SSR primer (Barbosa et al, 2006;Hatanaka et al, 2006, Morelli et al, 2007, thereby lowering the costs of future projects.…”
Section: Discussionmentioning
confidence: 99%
“…This would be most feasible with cultured species where parents and their progeny can be managed and traced within a closed system. It will be possible to use mapped genetic markers to trace the inheritance of specific chromosomal arms in progeny (Morelli, 2007). The polymorphism obtained with microsatellite markers have provided strong information utilized in the management of fish stocks (Alam and Islam, 2005).…”
Section: Monitoring Genetic Changes In Stocksmentioning
confidence: 99%
“…In the analyses of microsatellite loci of the groups of L. elongatus, eight flanking primer pairs constructed for microsatellite loci of Leporinus macrocephalus (Lmac) (Morelli et al, 2007) were screened. After adjustments of the DNA amplification conditions (concentration of the components of PCR reactions; time and temperature of the different steps in the amplification cycle), as well as the adjustments of electrophoretic analysis methodology, we selected five of these primers pairs for the Lmac 04, 06, 07, 08 and 09 loci.…”
Section: Rapd and Microsatellites Markers Dna Amplificationmentioning
confidence: 99%
“…Given that the development of primers can be costly, several studies have tested for possible heterologous amplifications in a target species using primers already described for evolutionarily related species (Cipriani et al, 1999;Brondani et al, 2003) or even for evolutionarily related genera (Zhan et al, 2009). Many studies have successfully demonstrated heterologous amplification (Barbosa et al, 2006;Hatanaka et al, 2006, Morelli et al, 2007, thereby lowering the costs of future projects. However, the loci detected by successful heterologous amplification should also be tested for their ability to access the polymorphism in the genome of the target species.…”
Section: Introductionmentioning
confidence: 99%